Dialogue - Heracleous, Loizos (Academy of Management Review, 2003)
The article presents views regarding the 2002 article ?Metaphor and Analogical Reasoning in Organization Theory: Beyond Orthodoxy,? by C. Oswick, T. Keenoy, and D. Grant. The article discusses the use of metaphor, metonymy and synecdoche to aid in knowledge generation, and argues that it is theoretically problematic to expect this tactic to be fruitful. The article states that metaphors are not based on high levels of similarity, and that they are not simple enough to help in idea generation because they create associations that are beyond target domains.